AUDIT KINERJA NON KEUANGAN TERHADAP KARYAWAN KANTOR KECAMATAN NGANJUK - Chrisma Putri Pertiwi; Indra Dekrijanti (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2018)
Non financial performance measurement can resolve the problems of financial performance measurement will be. Non financial performance measures focus on the long-term success and factors such as customer satisfaction, internal business process efficiency, innovation, employee satisfaction and lead to increased performance of organizations. the purpose of this research is to know how the performance audit non financial Office employees nganjuk sub-district based on the perspective of the customer, internal business processes, and learning and growth. Place of implementation research was in Office her Sub. This research includes research case studies with quantitative approach. The population in this study are all the employees and customers/community who get service. Samples of untuki employees are all employees used a sample, whereas customers used the formula slovin and obtained 57 respondents. Engineering data collection using the questionnaire, conducted test validity and reliability. data analysis using the criterion of performance is very good sampaisangat not good on a likert scale. The results of the research note that the assessment of the performance of non financial hole sub office employee was 78.27% with details of each perspective is the perspective of the internal business of 77.07% with quite a good category, perspective learning and growth of 77.00% by category is good enough, the customer perspective 80.74% with categories either. This shows that the performance of the non financial hole sub office employee are in a quite good. It needs to be improved is the understanding and capabilities of the employees in terms of computerization to facilitate their work, n recognition of the existence of a good working achievements, as well as granting data and clear information.